The Influence Of Leverage, Tax Planning, And Good Corporate Governance On Earning Management - Fathimah Fathimah; Retno Indah Hernawati; Imang Dapit Pamungkas; Lilis Setyowati (Jurnal Telekomunikasi dan Informatika, 2024)
Profit is a crucial indicator in assessing the financial performance of a company. One method that can be utilized to manipulate a company’s proft is through earning management. The objective of this study is to investigate and analyze how leverage, tax planning, and effective corporate governance impact earnings management. the study’s sample is chosen through purposive sampling, with a specific focus on state-owned enterprises (BUMN) . Employing a quantitive approach, regression analysis is utilized as the analytical method, and a total of 74 sample are included in this study. Statistical data analysis to test hypotheses is conducted using SPSS 24 software. The research results reveal that only one variable accepted, namely institutional ownership, which has a negative influence on earnings management. On the other hand, the hypotheses regarding leverage, tax planning, managerial ownership, and audit committee are rejected.